Detection of the Buckminsterfullerene Cation (C60+) in Space. Issue Volume 9:Issue S297(2013) (21st February 2014) - Berné, O.; Mulas, G.; Joblin, C.
Abstract: In the early 90's, C60 + was proposed as the carrier of two diffuse interstellar bands (DIBs) at 9577 and 9632 Å, but a firm identification still awaits gas-phase spectroscopic data. Neutral C60, on the other hand, was recently detected through its infrared emission bands in the interstellar medium and evolved stars. In this contribution, we present the detection of C60 + through its infrared vibrational bands in the NGC 7023 nebula, based on spectroscopic observations with the Spitzer space telescope, quantum chemistry calculation, and laboratory data from the literature. This detection supports the idea that C60 + could be a DIB carrier, and provides robust evidence that fullerenes exist in the gas-phase in the interstellar medium. Modeling efforts to design specific observations, combined with new gas-phase data, will be essential to confirm this proposal. A definitive attribution of the 9577 and 9632 Å DIBs to C60 + would represent a significant step forward in the field.